The storyteller : a novel - Picoult, Jodi, frey50 (New York : Emily Bestler Books/Atria, 2013)
Becoming friends with Josef Weber, an old man who is particularly loved in her community, Sage Singer is shocked when one day he asks her to kill him and reveals why he deserves to die, causing her to question her beliefs.
Keywords: Bakers; Friendship; Good and evil; Ex-Nazis; Psychological fiction; Psychological fiction